Electronic structure comparisons of isostructural early d- and f-block metal(iii) bis(cyclopentadienyl) silanide complexes. Issue 3 (13th December 2022) - Gransbury, Gemma K.; Réant, Benjamin L. L.; Wooles, Ashley J.; Emerson-King, Jack; Chilton, Nicholas F.; Liddle, Stephen T.; Mills, David P.
Abstract : We report an isostructural series of early metal complexes containing cyclopentadienyl (Cp)-supported M–Si bonds. Differences in the extent of metal–ligand covalency causes a magnetic anisotropy switch between d- and f-block metals. Abstract : We report the synthesis of the U(iii ) bis(cyclopentadienyl) hypersilanide complex [U(Cp′′)2 {Si(SiMe3 )3 }] (Cp′′ = {C5 H3 (SiMe3 )2 -1, 3}), together with isostructural lanthanide and group 4 M(iii ) homologues, in order to meaningfully compare metal-silicon bonding between early d- and f-block metals. All complexes were characterised by a combination of NMR, EPR, UV-vis-NIR and ATR-IR spectroscopies, single crystal X-ray diffraction, SQUID magnetometry, elemental analysis and ab initio calculations. We find that for the [M(Cp′′)2 {Si(SiMe3 )3 }] (M = Ti, Zr, La, Ce, Nd, U) series the unique anisotropy axis is conserved tangential to ; this is governed by the hypersilanide ligand for the d-block complexes to give easy plane anisotropy, whereas the easy axis is fixed by the two Cp′′ ligands in f-block congeners. This divergence is attributed to hypersilanide acting as a strong σ-donor and weak π-acceptor with the d-block metals, whilst f-block metals show predominantly electrostatic bonding with weaker π-components. We make qualitative comparisons on the strength of covalency to derive the ordering Zr > Ti ≫ U > Nd ≈ Ce ≈ La in these complexes, using a combination of analytical techniques. The greater covalency of 5f 3 U(iii ) vs. 4f 3 Nd(iii ) is found by comparison of their EPR and electronic absorption spectra and magnetic measurements, with calculations indicating that uranium 5f orbitals have weak π-bonding interactions with both the silanide and Cp′′ ligands, in addition to weak δ-antibonding with Cp′′.